Efeito da administração de melatonina na recuperação metabólica após exercício de natação em ratos - Cipriano, Alinson Eduardo (Universidade Federal de São Carlos, 2024)
Melatonin has the potential to act in the recovery process after physical exercise, however, there are no studies on the effects of this compound on energy metabolism and tissue damage after isoload exercise. In isoload exercise, animals are subjected to the same workload in all exercise sessions, ensuring greater uniformity in the physical stimuli applied. This study aimed to evaluate how melatonin administration after isoload exercise impacts energy metabolism and markers of tissue damage. Sixty Wistar animals were subjected to a 60 min swimming exercise at 90% of their maximum aerobic capacity (iMAC), followed by intraperitoneal administration of melatonin (EM; 10 mg.kg-1) or control (Ex) of the same volume and components, except melatonin, and after that, the animals were euthanized 1, 3 or 24 hours. Blood was collected to analyze the concentration of lactate dehydrogenase, creatine kinase, glucose and triglycerides; skeletal muscle tissue (white and red gastrocnemius, and gluteus maximus) and liver for quantification of glycogen content; (soleus, white and red gastrocnemius, and gluteus maximus) and liver for quantification of triglyceride content; skeletal muscle tissue (gluteus maximus) and liver for quantification of the pool of amino acids and acylcarnitines. Tissue samples were extracted and had their amino acid and acylcarnitine profiles determined using flow injection analysis (FIA) coupled to targeted mass spectrometry (MS). Data were presented as mean ± standard deviation of the mean, submitted to the Two-way ANOVA test and Newman-Keuls post hoc was used to analyze the effects of melatonin (two levels) and the effect of time (three levels). Effect size analysis and confidence interval were used as complementary tests. A significance level of 5% was adopted for all analyses, performed using Statistics 7.0 software (StatSoft, Inc.; Tulsa, OK, United States). The results were divided into two chapters. In chapter 1, animals treated with melatonin did not show any significant results in the hepatic amino acid pool, but in skeletal muscle, melatonin increased the pool of amino acids such as arginine (F = 13.27; p = 0.001), glutamic acid (F = 5.92; p = 0.023), citrulline (F = 10.72; p = 0.003), glutamine (F = 8.15; p = 0.009), ornithine (F = 4.88; p = 0.037), proline (F = 15.13; p = 0.001) and serine (F = 7.23; p = 0.013) in relation to the control. Melatonin also increased the glycine pool 3 hours post exercise compared to the control group (EM3>Ex3; p = 0.034) and reduced the methionine pool 24 hours post exercise compared to the control group (EM24<Ex24; p = 0.001) . In chapter 2, animals treated with melatonin did not show significant results for skeletal muscle and liver regarding the dynamics of the acylcarnitine pool. However, in serum concentrations, melatonin reduced the concentration of lactate dehydrogenase (F = 24.03; p = 0.000) and glucose (F = 11.01; p = 0.001), while creatine kinase (F = 2.44; p = 0.124) and triglycerides (F = 1.08; p = 0.304) remained unchanged. Melatonin also increased glycogen content for red gastrocnemius (F = 82.81; p = 0.000), gluteus maximus (F = 19.55; p = 0.000), liver (F = 6.24; p = 0.016), and reduce to the white gastrocnemius (F = 4.28; p = 0.044). Regarding tissue triglyceride content, in the presence of melatonin there was a reduction in the white gastrocnemius (F = 20.79; p = 0.000), red gastrocnemius (F = 8.76; p = 0.005) and gluteus maximus (F = 4. 90; p = 0.032), while it increased the soleus (F = 6.00; p = 0.019), with no effect on the liver (F = 3.44; p = 0.070). Therefore, the present study demonstrated that in the presence of melatonin after isoload exercise, there was an increase in the levels of some amino acids in skeletal muscle tissue. Furthermore, melatonin modulated energy metabolism through the reduction of glucose, muscle and plasma triglyceride levels and accelerated the replacement of muscle glycogen content, as well as decreasing tissue damage when assessed through the reduction of lactate dehydrogenase. In this way, the cellular environment was favored for future efforts, at least from a bioenergetic point of view.
Effect of melatonin administration on metabolic recovery after swimming exercise in rats
Efecto de la administración de melatonina sobre la recuperación metabólica después del ejercicio de natación en ratas
Keywords: Recuperação após exercício; N-acetil-5-metoxitriptamina; Aminoácidos; Acilcarnitinas; Nutrição; Natação; Fisiologia do exercício; Recovery after exercise; N-acetyl-5-methoxytryptamine; Amino acids; Acylcarnitines; Nutrition; Swimming; Exercise physiology; CIENCIAS BIOLOGICAS; CIENCIAS DA SAUDE::EDUCACAO FISICA